Pomoči politike trga dela - Česen, Tanja (Gospodarska gibanja, 2009)
Labor market policy supports are designed by the state for redundant workers and unemployed as a compensation for the loss of incomes. Supports represent security in the new concept of 'flexicurity'. Developed European countries have built wide variety of supports, which are designed for people, who are seeking job, wish to work, and are capable to work. The list of EU supports is extensive: unemployment benefits and assistance, redundancy compensations, bankruptcy compensations, and early retirement. In Slovenia, a former socialist country, we nowadays have only unemployment benefits.
Keywords: brezposelni; socialna pomoč; trg delovne sile